The Secret Valley Divided: Administrative Proliferation In Kerinci Valley, Jambi Province, Sumatra, Indonesia - Bettinger, Keith Andrew (Journal of Rural Indonesia [JORI], 2013)
After the fall of president Suharto Indonesia implemented sweeping decentralization reforms with the goal of rebalancing powers and responsibilities between the central government and the regions. Among the raft of new laws was legislation that allowed for increased proliferation (pemekaran) at the district/municipality and provincial level. In theory administrative proliferation would increase citizen participation and efficiency in governance. After 12 years the number of districts in Indonesia has nearly doubled, but there are indications that the performance of new regions is not living up to expectations. This paper examines one case: the creation of the administrative municipality of Sungai Penuh, which was split off from Kerinci District, Jambi Province, Sumatra, in 2009. I find that the process of new region creation in Kerinci has been dominated by local elites and has actually decreased unity within the district and has given rise to a movement to further sub-divide the district. The implementation of pemekaran created new tensions, and very likely will undermine the medium and long-term prospects for development in the region. © 2013 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Keywords: administrative proliferation; decentralization; indonesia; elite capture; reformasi